Vineland Adaptive Behavior Scale in a Cohort of Four ADNP Syndrome Patients Implicates Age-Dependent Developmental Delays with Increased Impact of Activities of Daily Living - Levine, Joseph; Hakim, Fahed; Kooy, R. Frank; Gozes, Illana (Journal of molecular neuroscience, 2022)
Activity-dependent neuroprotective protein (ADNP) is one of the lead genes in autism spectrum disorder/intellectual disability. Heterozygous, de novo ADNP mutations cause the ADNP syndrome. Here, to evaluate natural history of the syndrome, mothers of two ADNP syndrome boys aged 6 and a half and two adults aged 27 years (man and woman) were subjected to Vineland III questionnaire assessing adaptive behavior. The boys were assessed again about 2 years after the first measurements. The skill measures, presented as standard scores (SS) included domains of communication, daily living, socialization, motor skills and a sum of adaptive behavior composite. The age equivalent (AE) and growth scale values (GSV) encompassing 11 subdomains assess the age level at which the subject’s raw score is found at a norm sample median and the individual temporal progression, respectively. The norm referenced standard scores age-matched, mean 100 ± 15 of the two children showed the lowest outcome in communication (SS: 20–30). Daily living skills presented SS of 50–60, with a possible potential loss of some activities as the child ages, especially in interpersonal relationships with people outside of the immediate family (boy A). In contrast, in socialization, both children were at the SS of 38, with some positive increase to SS of ~ 45 (interpersonal relations with family members and coping skills, depending on the particular individual), 2 years later. Interestingly, there was an apparent large difference in motor skills (gross and fine) at the young age, with subject B showing a relatively higher level of skills (SS: 70), decreasing to subject A level (SS: 40) 2 years later. Together, the adaptive behavior composite suggested a level of SS: 39–48 with B showing a potential increase (SS: 41–44) and A, a substantial decrease (SS: 48–39), suggesting a strong impact of daily living skills. Adults were at SS: 20, which is the lowest possible score. AE showed minor improvements for subject A and B, with all AE values being below 3 years. GSVs for subject A showed some improvement with age, especially in interpersonal, play and leisure, and gross motor subdomains. GSV for subject B showed minor improvements in the various subdomains. Notably, all subjects showed a percentile rank < 1 compared with age-matched norms except for subject B as to motor domain (2 nd percentile) at the age of 6 years. In summary, the results, especially comparing SS and AEs between childhood and adulthood, implied a continuous deterioration of activities compared to the general population, encompassing a slower developmental process coupled to possible neurodegeneration, strongly supporting a great need for disease modifying medicinal procedures.